Chemical studies in some woodland soils from north-east Scotland - Muir. Alex (The University of Edinburgh, 1934)
1. The seasonal fluctuations in the nitrate and ammonia content of some soils from Boghall Glen have been studied. 2. There is no very marked increase in the nitrate content in spring, but in late summer the increase is very marked. 3. This summer increase in nitrate content appears to be connected with the much higher temperature prevailing in that season. 4. The relation of nitrifying powers to the quality of the pasture is discussed.